Modelos de programação inteira mista para a alocação ótima de bancos de capacitores em sistemas de distribuição de energia elétrica radias - Ribeiro, Érica Tatiane Almeida [UNESP] (2013)
This work shows the development of a mixed integer linear programming model and a mixed integer second-order conic programming model to solve the allocation problem of fixed or switched capacitors banks in radial electrical distribution systems, with the aims to improve the voltage magnitude profile and minimize the energy losses and investment costs. In the proposed models, the steady-state operation point of the radial distribution system is modeled through linear and second-order conic expressions. The use of a mixed-integer linear programming model and a second-order conic programming model guarantee convergence to optimality using existing optimization software. The test systems of 70, 136, 202 and 400 nodes are used in order to show the accuracy of the mathematical models, as well as the efficiency of the proposed solution technique to solve the allocation problem of fixed or switched capacitors banks in a radial distribution system.